Determination of matching problems for integrated programs of early grain harvest - Сидорчук, Олександр Васильович; Тригуба, Анатолій Миколайович; Макарчук, Олексій Васильович; Скібчик, Володимир Іванович (Eastern-European Journal of Enterprise Technologies, 2012)
The necessity of matching problems for integrated programs of early grain harvest in Ukraine is grounded. The classification of management tasks on integrated programs of early grain harvest is done. The matching problems of product and service projects in early grain harvest programs are marked